SO2 conversion to sulfones: development and mechanistic insights of a sulfonylative Hiyama cross-coupling. Issue 86 (10th October 2019) - Adenot, Aurélien; Char, Joëlle; von Wolff, Niklas; Lefèvre, Guillaume; Anthore-Dalion, Lucile; Cantat, Thibault
Abstract : A Pd-catalyzed Hiyama cross-coupling reaction using SO2 is described. Abstract : A Pd-catalyzed Hiyama cross-coupling reaction using SO2 is described. The use of silicon-based nucleophiles leads to the formation of allyl sulfones under mild conditions with a broad functional group tolerance. Control experiments coupled with DFT calculations shed light on the key steps of the reaction mechanism, revealing the crucial role of a transient sulfinate anion.